“It’s a good fucking story”: Journalistic routines, roles, and actions in the series The Wire - Lagos-Olivero, Claudio Adrián (Re-presentaciones: Periodismo, comunicación y sociedad, 2025)
This article examines how journalistic roles, routines, and practices are represented in the fifth season of HBO’s series The Wire, which focuses on the newsroom of The Baltimore Sun newspaper. Using a qualitative approach that combines content, semiotic, and narrative analysis, it explores professional practices, ethical tensions, and the structural transformations of U.S. journalism. The study highlights the role of the editor as a key gatekeeping actor who defends journalistic ethics. The series is interpreted as a profound critique of the deterioration of the traditional press, showing that, despite a context of ongoing change and structural crisis, ethical and high-quality journalism remains possible .